The Prevalence of Low Vitamin D in Elite Para-Athletes: A Systematic Review - Christina Kate Langley; Christopher Ian Morse; Aidan John Buffey (SpringerOpen, 2024)
Abstract Background Vitamin D insufficiency (25OHD, 50-75 nmolˑl− 1) is a common issue within healthy adults and elite athletes and is associated with decreased musculoskeletal health and performance. However, few studies have identified the prevalence and risk factors associated with vitamin D insufficiency within elite Para-Athletes. Methods An electronic search was completed on the 5th January 2023 and updated on the 21st June 2024, searching Web of Science, PubMed, Scopus, Cochrane Library and EASY (originally OpenGrey). To meet the eligibility criteria, retrieved studies were required to include at least one baseline measure of a vitamin D biomarker from elite Para-Athletes performing at national or international levels and therefore all quantitative study designs could be included. Risk of bias was assessed using the Joanna Briggs Institute Critical Appraisal Checklist (8-item) for analytical cross-sectional studies. Data from the eligible studies was extracted and charted, with a supporting narrative synthesis. Results The search strategy retrieved 3083 articles, of which ten studies met the inclusion criteria. In total there were n = 355 Para-Athletes, 69.6% of which comprised of males in the included studies. Across the ten included studies, n = 546 samples were taken from n = 355 Para-Athletes across different seasons and based upon the 25(OH)D insufficiency and deficiency thresholds set by each individual study 43.2% of the samples were considered insufficient and 28.1% deficient. During the winter months vitamin D insufficiency was at its most prevalent at 74.1%, compared to 57.1% in summer of the 25(OH)D samples measured in Para-Athletes. Wheelchair athletes who competed in indoor sports were also more susceptible to low vitamin D. Conclusion This review has highlighted that vitamin D insufficiency and deficiency is highly prevalent in elite level Para-Athletes, all year, across both summer and winter months. Therefore, this review highlights the need for education, treatment, and preventative measures in elite Para-Athletes throughout the year. Registration The following systematic review was prospectively registered through PROSPERO International prospective register of systematic reviews (PROSPERO registration ID number: CRD42022362149).